Assessment of the phytoremediation potential of lycianthes lycioides (L.) hassl (2017)
The river Bogotá and its banks show a high contamination by heavy metals like chrome, arsenic, etc., being impacted for decades by anthropic activities including those of tanneries near its source. To restore these riverside soils phytoremediation is employed, which has many socio-economic advantages. Aim: to determine the phytoremediation capacity of the species Lycianthes lycioides (L.) Hassl, located in the upper part of the basin of the river Bogotá. Methods: the species which were to be evaluated were gathered in the town of Villapinzón, located at 05° 07’ 23.4”N and 73° 39’ 10.5”W., which is regarded as a highly contaminated area due to the presence of tanneries, and also in the town of Tenjo, at the Cerro de la Punta. The study employed an acid digestion procedure (using HNO3: HCl 1:1), with a subsequent quantification of metals like Cd, Cr, Co, Pb and As by the atomic absorption technique with a VARIAN AA140 spectrophotometer. Results: for the species collected in Tenjo the concentrations found were: Leaves: mg/Kg; Cd: 3.58; Cr: 0.05; Co: 2.20; Pb: 3.01; As: 4.94. Stems: mg/Kg; Cd: 4.73. Cr: 0.60. Co: 0.84; Pb: 3.18; As: 20.52. Root: mg/Kg; Cd: 5.65; Cr: 2.51; Co: 0.58; Pb: 3.77; As: 21.53. Soil: mg/Kg; Cd: 7.29; Cr: 3.68; Co: 2.92; Pb: 4.60; As: 28.16. For the species collected in Villapinzón, the concentrations found were: Leaves: mg/Kg; Cd: 8.02; Cr: 6.55; Co: 2.85; Pb: 7.63; As: 88.43. Stems: mg/Kg; Cd: 7.74; Cr: 6.70; o: 1.05; Pb: 7.38; As: 118.13. Root: mg/Kg; Cd: 7.87; Cr: 6.75; Co: 0.93; Pb: 7.78; As: 183.88. Soil: mg/Kg; Cd: 33.95; Cr: 151.14; Co: 16.53; Pb: 45.02; As: 195.84. Conclusions: it was demonstrated that the Lycianthes lycioides (L.) Hassl. collected in Villapinzón accumulates a high proportion of chrome and arsenic in its different organs and this confirms its potential for phytoremediation.